The FAKTOR-FAKTOR YANG MENYEBABKAN MASALAH PSIKOSOSIAL PADA IBU DENGAN ANAK RETARDASI MENTAL DI SLB SE KOTA PADANG - Linda Andriani (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2021)
The birth of a child with growth and developmental disorders can cause psychosocial problems in the mother. Where mothers who have children mental retardasi experience stress, anxiety and depression. Several studies were obtained by the parents of children with mental retardation, of which 102 received 65 mothers of stress, 50% of mothers experienced ansieta and 52.94% of mothers experienced depression. This study aims to analyze the factors associated with psychosocial problems in mothers of mental retardation children in SLB in Padang city. Descriptive analytic research design, cross sectional approach. A sample of 267 mothers with mentally retarded children in SLB in Padang city with proportionate stratified random sampling. The result of the research is there is a significant relationship between work, marital status and self-concept with stress on mother, there is a significant relationship between income and marital status with ansietas and there is a significant relationship between income and marital status with depression in mothers who have children mental retardation. Nurse of the soul is very necessary in overcoming the problem of stress, anxiety and depression so that mother can better accept condition of child problem which mother face.